BLT Temporary Unconditional Cash Transfer - World Bank (World Bank, Jakarta, 2017)
The Bantuan Langsung Tunai (BLT) program had a clear and modest objective: supplement consumption for poor households facing unprecedented price increases. In 2005 subsidy cuts raised household fuel prices by an average of over 125 percent with 88, 186, and 105 percent increases in gasoline, kerosene, and solar (diesel) fuels respectively. BLT, a direct cash transfer in four installments over one year, funded from the implied budgetary savings from subsidy reductions, was in many respects the most significant Government of Indonesia (GOI) response to these programmed increases in fuel prices. It was targeted to the poor households who were benefiting least from the old subsidy regime and most at risk from the negative impacts on consumption from price increases. A mostly-similar BLT was introduced again in 2008 when international crises in both financial markets and in food prices combined with another domestic reduction to fuel subsidies. BLT provided just-in-time cash assistance to households affected by an economic shock. BLT added cash amounts to a household's budget equal to approximately 15 percent of regular expenditures in 2005. These transfers were more than enough to cover increased expenditure on fuels. Benefits continued for one year as shocks from government policy reverberated through the rest of the macro-economy, allowing beneficiaries time to readjust spending patterns to new relative prices.